COLLABORATION BETWEEN SCHOOLS, FAMILIES, AND COMMUNITIES IN ISLAMIC EDUCATION MANAGEMENT - Moh. Kamil; Abdullah Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the forms, strategies, and effectiveness of collaboration between schools, families, and communities in supporting holistic Islamic education management. This collaboration is considered crucial for realizing education that is not only oriented towards knowledge, but also towards the development of Islamic morals and character in students. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation at several Islamic educational institutions. Data analysis was conducted interactively through the stages of reduction, presentation, and drawing conclusions. The results show that the active involvement of families and communities in the planning and implementation of school activities has a positive effect on improving the quality of education and fostering students' morals. Furthermore, good communication between these three elements creates a harmonious, religious, and productive educational atmosphere. The implications of this study emphasize the importance of participatory and collaborative Islamic education management in developing a generation of faith, knowledge, and noble character